The Impact of the Determination of the Mamminasata National Strategic Area on Rice Fields in Maros Regency - Yunito, Muhammad Rahmanda; Barus, Baba; Trisasongko, Bambang Hendro (Jurnal Planologi, 2025)
The Integration of the Mamminasata National Strategic Area (KSN), encompassing Maros, Gowa, Takalar, and Makassar City, significantly impacts productive rice fields, particularly in Maros Regency. This study evaluates the effects of KSN designation on rice fields by analyzing spatial planning policies, farmers perceptions of rice field protection, and changes in rice field area from 2007 to 2024 using Boolean overlay, interview and image interpretation. The research reveals that only 58.57% of rice fields complies to either KSN or spatial planning (RTRW), highlighting the need for spatial plan policy synchronization. Most farmers were landowners and cultivators over 50 years old, with limited interest among younger generations to continue farming. Farmers have heavily relied on agriculture as their primary livelihood, yet their awareness of the Protected Rice Field (LSD) policy remained low, especially on easily convertible lands. Majority of farmers supported rice field protection and agreed to LSD designation, hoping for assistance and incentives. This research found that rice field areas continued to decline due to urban expansion driven by population growth, infrastructure development, and national strategic projects, especially near Makassar City. Integrated policies are therefore essential to sustain agriculture and farmer welfare.